Impact of Industry and Export on the Biomass Resources - Kaur, Rajinder Pal (International Journal of Advanced Science and Technology, 2019)
In this paper, we have proposed and analyzed a nonlinear mathematical model to study the pattern of depletion of forest biomass due to industry and export. The existence of equilibria and their local stability under certain conditions have been discussed. We have carried out the Hopfbifurcation analysis by considering government control as a bifurcation parameter as government vigilance for the protection of forest biomass has been remained an important factor. Moreover, the direction of Hopf-bifurcation is determined using the center manifold theorem. We have obtained the threshold values of certain constraints (government control) imposed on export and industry growth, for the sustainable development of forest biomass. Finally, all the analytical ﬁndings are properly validated using numerical simulation.